THE DEVELOPMENT OF CAREGIVERS’ KNOWLEDGE ABOUT STROKE AND STROKE CAREGIVING SKILLS TOOLS FOR STROKE CAREGIVERS IN INDONESIA - Sukron, .; Phutthikhamin, Nichapatr (LIFE: International Journal of Health and Life-Sciences, 2016)
This descriptive research aimed develop caregiver’s knowledge about stroke and stroke caregiving skills tools. The study samples are caregivers of stroke patients at Neurological outpatient unit of Muhammadiyah Hospital Palembang, South Sumatera,Indonesia. Content validity was tested by five experts and Reliability was tested in 30 stroke caregivers.The reliability was tested using SPSS and internal consistency would be analyzed by KR-20 (Kuder-Richardson 20). The finding of content validity showed that stroke diseasedimensions’ there were four items not agreed by expertsI-CVIs = 0.80, however another items was agreed by all experts I-CVIs = 1.00. Mean of I-CVI for all experts were 0.92. The experts mentioned that the stroke dimensions were clear and relevant to assess caregiver knowledge about stroke. In reliability test, the mean score was 11.73 (SD=4.75) with variance 22.55 and KR-20 was 0.75. For stroke caregiving skills, mean of I-CVI for all experts were 0.90. In reliability test, using cronbach’s alpha was 0.75. In conclusion, the caregivers’ knowledge about stroke and stroke caregiving skillshave good properties to assess the level of knowledge about stroke and skills for stroke caregiver. Nurses who work with stroke patients oninpatient unit can use the tool to assess caregiver knowledge and skills before discharge at home. Further study should examine and modified the same tools with different setting, method, and add more sample size.